VD_FINDINFO MP / 2010 / 24 vom 15. November 2010 - VD Tribunal cantonal (2010)
DISSOLUTION DE LA SOCIÉTÉ, SOCIÉTÉ ANONYME, LÉGITIMATION ACTIVE ET PASSIVE | 736 ch. 4 CO, 736 CO, 101 al. 1 ch. 1 CPC, 101 al. 1 ch. 2 CPC